(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article examines a collection of archival documents housed in the Manuscripts Division of the Biblioteca Nacional do Rio de Janeiro, which detail a dispute over wage payment in a theatre at the Imperial Court. The case focuses on the lyric soprano Augusta Candiani and the actor João Caetano dos Santos, who held the position of director of the Teatro Provisório in 1853. Among these documents is a contract between the singer and the theatre. This previously unpublished source provides valuable insights into the dynamics of labor relations, as well as the rights and responsibilities that shaped professional theatre in the 19th century.